Transformational changes in the economy in the context of the development of digital business models: influence factors, problems, prospects - Ianenko Marina; Ianenko Mikhail (π-Economy)
Transformation of economic management processes has become a crucial direction against the background of fierce competition and explosive rise of digital technologies in various industries. The significance of this problem in the context of the development of digital business models radically changing the situation in a number of economic sectors is linked with the demand for new approaches to improve enterprise management, create and develop innovative tools ensuring competitiveness in the digital economy. The goal of the study is to generate new approaches to management of transformational changes within the framework of modern business models, offering practical recommendations for the development of competitive strategies. The work uses methods of system analysis, structural and logical analysis, content analysis, as well as economic and statistical methods, methods of comparative analysis, forecasting and expert assessments. The classification of digital business models developed by the authors allows to formulate recommendations for using the concept of digital business models in managing the digital transformation of enterprise activities. The directions proposed for constructing the concept of managing the transformation of activities in the digital economy allow to account for: potentially providing consumers with additional free services in exchange for receiving data on their consumer behavior; network effects; role of digital technologies as a source of innovation. Recommendations are given for using digital business models together with marketing tools in the activities of the enterprise associated with promoting material, digital and virtual products, including in metaspatial business entities. The scientific novelty of the work lies in combining the concept of digital business models with marketing tools when analyzing the processes occurring in the digital economy. Specific examples illustrate the transformations occurring under the influence of digital business models, recommendations are given for the formation of strategies in a changing competitive environment. It is confirmed that the development and implementation of innovative business models requires engaging marketing specialists and integrating marketing tools. Further research is expected to focus in-depth analysis of the impact of digital business models on the improvement of product and pricing policies, sales systems and product promotion in the context of the development of artificial intelligence.